Analisis Sifat Fisik dan Mekanik Poros Berulir (Screw) Untuk Pengupas Kulit Ari Kedelai Berbahan Dasar Aluminium Bekas dan Piston Bekas - Wisnujati, Andika; Hafiz, Lalu Alpan (INTEK: Jurnal Penelitian, 2017)
Aluminum alloys in this study using a mixture of aluminum profiles and former piston. Former piston is used to get the high enough of element Si. The addition of TiB element (Titanium-Boron) as much as 0.02% at the time of casting expected to improve the mechanical and physical character of aluminum, so that expected the aluminum alloy has a strength that is much better than without the addition of any element. Aluminum alloy to manufacture screw will be casted by using sand molds on three types of variations mold temperature 200oC, 300oC and 400oC. The Test were conducted to determine the mechanical properties of the aluminum alloy and physical that are : tensile test, hardness test, and metallographic with an optical microscope. The maximum test result occurred in Al-Si alloy material with TiB addition 0.02% and a heating temperature mold 400oC produces maximum tensile stress of 628.86 N / mm², while for Vickers Hardness Number (VHN) gives the figure of 114 kg / mm2; and for the results obtained from the data metallographic structure formed hypereutectic silicon which form the primary silicon phase. That phase provides high wear resistance. Finally, it is evident that the Al-Si alloys mentioned above can improve the properties of aluminum to manufacture a screw.